Patterns of alcohol use: a two-year college and four-year university comparison case study. Issue 1 (2nd January 2016) - Cremeens-Matthews, Jennifer; Chaney, Beth
Abstract: With more than 12 million students enrolled in over 1, 150 two-year institutions, enrollment at these institutions constitutes approximately 44% of all undergraduates in the United States. Despite this, research and prevention efforts related to drinking behaviors among college students attending two-year institutions are limited, with similar information regarding students at traditional four-year institutions readily available. This study sought to examine alcohol use patterns among students at a two-year college compared to a four-year institution. It was conducted at a large (20, 000+ students), public, four-year institution and a medium (8, 000+), public, two-year institution located in the same community. The Core Alcohol and Drug Survey, a 39-item instrument used by colleges and universities for assessing the nature, scope, and consequences of high risk drinking behaviors in college students, was administered to students at both a two-year ( n = 581) and a four-year institution ( n = 928) (Cremeens & Chaney, 2012). The prevalence estimates of current alcohol use among students at the two-year institution in this study are comparable to national estimates for students attending four-year institutions (67.5% and 69.0%, respectively). Estimates of high-risk alcohol use at the four-year institution in this study were higher than national prevalence estimates for similar colleges. Current drinkers and binge drinkers at both institutions experienced the same negative consequences. While the study results provide insight into the need for alcohol prevention efforts at community colleges, there are important factors and practical considerations related to these efforts presented here for community colleges and administrators to contemplate.